Musafir Ilmu Apps Development Using Mobile Application Development Life Cycle - Azma Nasruddin, Zan; Mazlin, Irwan; Abdul Aziz, Maslina; Shukor Abd Rahman, Mohd; Adilah Wan Adnan, Wan (International Journal of Engineering and Technology, 2018)
The presence of mobile wireless technology has changed the current learning culture environment. Today, smartphone has become an essential device for effective learning. Many mobile apps have been developed covering digital contents for all sorts of disciplines. This paper presents the development of mobile application for Muslims which is focusing on Hijaiyyah pronunciation.  This application is named Musafir Ilmu Application with aims to help improve the learning process of Hijaiyyah pronounciation. The Mobile Application Development Life Cycle is employed in the development of the apps. This application has been tested on 32 UiTM students by observation method. Performance of the application is measured using Confusion matrix which calculate the precision and recall rates. The results have indicated the app is an effective learning tool.